Tinjauan Bentuk dan Estetika Font Bergaya Aksara Jawa - Arief, Lukman (Universitas Dinamika, 2025)
Research on the review of the form and aesthetics of Javanese script-style fonts can be crucial in developing better Javanese script fonts that align with user needs. Javanese script fonts are an important aspect of preserving Javanese script culture, and their usage is increasingly growing in the digital context. In this study, researchers can analyze the form of Javanese script fonts, such as letter characteristics, spacing, kerning, and proportions. Additionally, the study may involve assessing the aesthetics of Javanese script fonts, including font selection and overall design. This research also includes a study of the history and development of Javanese script fonts to gain a more contextual understanding of font design. The study employs qualitative methods, such as interviews with users of Javanese script fonts or visual analysis, and quantitative methods, such as surveys on Javanese script font preferences. The results of this study can provide significant benefits for the development of better Javanese script fonts that meet user needs and strengthen the cultural identity of the Javanese script. This research can also contribute significantly to the preservation and development of local culture.